Microbial Phenazines Biosynthesis, Agriculture and Health - Chincholkar, Sudhir; Thomashow, Linda; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Microbial Phenazines: Biosynthesis, Agriculture and Health focuses on phenazines, a group of upwards of a hundred nitrogen-containing redox-active heterocyclic compounds of bacterial origin that have long attracted scientific interest because of their colorful pigmentation. Our understanding of these fascinating natural products and their role in human health and the environment has advanced rapidly in recent years, but we are only now beginning to be able to exploit the potential of these compounds in such fields as agriculture and medicine. This volume includes information on the biochemistry and genetics of phenazine synthesis, the physiological effects of phenazines, and methods for the isolation and identification of phenazines with the aid of spectroscopic and electrophoretic techniques. Also included are chapters focused on the roots of phenazine research in the biological control of plant pathogens and recent knowledge of the diversity of phenazine-producing microorganisms and the environments in which they occur. A final chapter addresses the potential of phenazines in the treatment of cancer.
The Biosynthesis of Phenazines -- Regulation of Phenazine Biosynthesis -- The Yin and Yang of Phenazine Physiology -- Phenazines and Bacterial Biofilms -- Fermentative production of bacterial phenazines -- Methods for Purification and Characterization of Microbial Phenazines -- Roles and Regulation of Phenazines in the Biological Control Strain Pseudomonas chlororaphis 30-84 -- Role of Phenazine-1-carboxamide Produced by Pseudomonas chlororaphis PCL1391 in the Control of Tomato Foot and Root Rot -- Genomic Features and Regulation of Phenazine Biosynthesis in the Rhizosphere Strain Pseudomonas aeruginosa M18 -- Phenazines in the Environment: Microbes, Habitats, and Ecological Relevance -- Phenazine as an anti-cancer agent.
Keywords: Life sciences; Toxicology; Biochemistry; Microbiology; Plant diseases; Life Sciences; Microbiology; Biochemistry, general; Plant Pathology; Pharmacology/Toxicology.